mGluR5 in amygdala modulates fear memory generalization - Xuan, Shou-Min; Su, Ya-Wen; Liang, Yi-Meng; Gao, Zhen-Jie; Liu, Chun-Yan; Fan, Bu-Fang; Shi, Yan-Wei; Wang, Xiao-Guang; Zhao, Hu (Frontiers in Behavioral Neuroscience, 2023)
Fear memory generalization is regarded as the core characteristic of PTSD development. However, the mechanism that contributes to the generalization of conditioned fear memory is still unclear. The generalization is generally considered to be a mismatch that occurs during memory consolidation. We showed here that fear conditioning using foot shocks of different intensities caused incremental generalization, which was clearly observed during training. Meanwhile, the density of c-Fos+ cells or the synaptic p-NMDAR expression did not differ with stress intensities. However, strong-shock fear conditioning could induce significant mGluR5 de novo synthesis in the amygdala, which was not observed in the weak-shock group. Inhibition of mGluR5 impaired fear memory generalization induced by strong-shock fear conditioning, but the generalization level induced by weak-shock training was enhanced. Taken together, these results indicated that mGluR5 in the amygdala is critical to the function of inappropriate fear memory generalization and suggested that this may be a potential target for the treatment of PTSD.